A study of cloud microphysical processes and a mesoscale environment in a heavy rainfall case over Yan’an - Xu, Jin; Ping, Fan; Li, Jian Yang; Du, Han (Frontiers in Earth Science, 2023)
A cloud-resolved numerical simulation was carried out for an extreme rainfall case in Yan’an, a city in arid and semi-arid regions in northwest China, on 3–4 September 2021,by using Mesoscale Weather Research and Forecasting Model. The Auto Weather Station and Doppler radar were applied to verify simulated results. The characteristics of mesoscale cloud environment and cloud microphysical processes were analyzed. Then, the quantitative rainwater mass budget and latent heat budget of microphysical conversions about water condensates calculated in Yan’an. The possible mechanism by which cloud microphysics affected the rainstorm was investigated and discussed. It was found that：(1) There was positive feedback between mesoscale cloud environment and cloud microphysical processes, especially non-adiabatic heating processes due to ice phase particles conversions. (2) The process of snow conversions processes was the most important process of this heavy rainfall in Yan’an.It not only promoted the production of rain , but also contributed to the enhancement of updraft through latent heat release and produced positive feedback to other microphysical processes in cloud. (3) Heavy rainfall in arid regions of China is mostly cold-type precipitation, mainly manifested by snow-dominated cloud microphysical processes producing deep convection.